Comments about the comparative bulk RNA sequencing between palmoplantar pustulosis and dyshidrotic palmoplantar eczema [version 1; peer review: 2 approved] - Masamoto Murakami; Jun Muto; Kazuki Yatsuzuka (F1000Research)
This correspondence discusses the recent findings by Straalen et al., highlighting molecular similarities and distinctions between palmoplantar pustulosis (PPP) and dyshidrotic palmoplantar eczema (DPE). The study emphasizes shared proinflammatory pathways and T-cell–related gene upregulation while detailing unique features such as neutrophil involvement in PPP and lipid antigen processing in DPE. We elaborate on histopathological differences, especially intraepidermal vesicle formation in PPP linked to IL–1–mediated pathways and the absence of hyaluronan expression, contrasting with Th2 cytokines-driven spongiosis in DPE. By addressing IL-4, hyaluronan synthases, and keratinocyte adhesion molecules, this correspondence aims to deepen understanding of PPP and DPE pathophysiology.